The Effect of Political Events on United States Direct Foreign Investment: A Pooled Time-Series Cross-Sectional Analysis - Nigh, Douglas (Journal of International Business Studies, 1985)
This paper examines the effect of political events on the manufacturing direct foreign investment (MDFI) decisions of U.S. multinational corporations. The relationship between political events (and nonpolitical factors) and MDFI is investigated through regression analysis of pooled time-series (21 years) and cross-sectional (24 countries) data and through various tests of the homogeneity of the relationship across groups of countries. The study finds that the relationship between political events in MDFI is different for less developed countries as opposed to developed countries. For the less developed countries, both inter-nation and intra-nation conflict and cooperation affect MDFI. In contrast, U.S. MDFI in developed countries appears to be affected only by inter-nation conflict and cooperation.